REVIEW OF THE HISTORY OF THE KYRGYZ NATIONALITY IN THE WORK OF Z.MAGZUNI «HISTORY OF THE KINGS OF FERGANA» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article discusses the history of the Kyrgyz people and Kyrgyzstan, illuminated in the manuscript “The History of the Rulers of Fergana” by Ziyabidin Magzuni, who served as a clerk in the Palace of the king of the Kokand Khanate(Kingdom) of the 19th century, written in the periods of 1865-1888. preserved in the library of Istanbul, with a volume of 883 sheets, that is, 1666 pages. Researched, analyzed and given a scientific assessment of the information about the Kyrgyz and the history of Kyrgyzstan mentioned in the manuscript.
Keywords: Khanate (Kingdom) of Kokand, Polot Khan, Muzafar Shaa, Ziyabidin Magzuni, Makhram, Boto-Kara, Minbash, Datka, Ordo, Kyrgyz, Kypchak.